PEMBERDAYAAN SDM KOMUNITAS KERUPUK KERANG MELALUI EDUKASI PRODUKTIVITAS DAN PENGUATAN MANAJEMEN USAHA - Yeni Mulyani; Dede Sujanah; Andini Awaliyah; Siti Nurmalasari; Ikaf Fandulu; Mohammad Hakim Mustaqim (Yayasan Nusa Cendekia Global, 2026)
Bintulan Village, Pandeglang, Banten has the potential for a shellfish cracker business that is managed from generation to generation. However, business actors still face obstacles such as low HR productivity, lack of understanding of business management, non-optimal financial management, and traditional marketing. This Community Service Program (PKM) aims to empower the HR of the shellfish cracker community through productivity education and strengthening business management. The implementation method uses a Community-Based Participatory Research (CBPR) approach through the stages of observation, socialization, training, mentoring, and evaluation. The material provided includes improving work productivity, simple financial management, digital marketing strategies, product innovation, and strengthening business management based on local potential. The results showed an increase in participants' understanding of work productivity, the importance of financial records, and the use of social media for marketing. This activity succeeded in increasing community knowledge and skills in managing businesses in a more structured and sustainable manner.